Cell surface properties of organic solvent-tolerant mutants of Escherichia coli K-12. - Aono, R (1997)
In this study, we examined cell surface properties of mutants of Escherichia coli for which organic solvent tolerance levels were elevated. The cell surface of each mutant was less hydrophobic than that of the parent, probably due to an increase in lipopolysaccharide content. OmpF synthesis was repressed in the mutants. Organic solvent bound readily to viable E. coli cells in response to the polarity of the solvent. The mutants were bound less abundantly with the organic solvent than was the parent.